AI as a Colleague: A Representative Employee Survey on Artificial Intelligence in the German Workplace - Pfeiffer, Sabine (Springer Fachmedien Wiesbaden, 2024)
Although there is a broad debate on the implications of artificial intelligence (AI) for work and society, far less research has been done into employees’ attitudes towards the use of AI in their immediate working environment. The article presents results of a representative survey with n = 2018 employees in Germany. One part of the survey utilised an interactive, ipsative survey tool based on Q-methodology which helps to capture more complex attitudes than conventional survey methods. Using multivariate analysis, four attitude types could be identified: the trouble-jugglers, the work-focused, the responsibility-takers and the relief-seekers. Despite other differences like gender or age, the results show that the most important factor for understanding attitudes towards AI is the work context. Furthermore, employees appear to be less worried and fearful about AI than is usually assumed, and they express a clear desire for more participation and a greater say in decisions about AI.
CRIS-Team Scopus Importer:2025-07-10
Keywords: Artificial intelligence; Employee survey; Q-method